Enhanced Lineage‐Specific Differentiation Efficiency of Human Induced Pluripotent Stem Cells by Engineering Colony Dimensionality Using Electrospun Scaffolds. Issue 12 (17th May 2016) - Maldonado, Maricela; Ico, Gerardo; Low, Karen; Luu, Rebeccah J.; Nam, Jin
Abstract : Electrospun scaffolds with varied stiffness promote distinct colony morphology of human induced pluripotent stem cells, which affects their subsequent differentiation . On soft scaffolds, induced pluripotent stem cells develop 3D colonies due to the pliability of the electrospun fibrous networks, leading to greater differentiation tendency to ectodermal lineage.